Substantial Out-of-Pocket Health Expenditure on Prenatal Check-Ups: Estimates from a Sample of Pregnant Women in Cartagena, Colombia - Alvis-Zakzuk NJ; Díaz-Jiménez D; Chaparro-Narváez P; Gutiérrez-Clavijo JC; Castillo-Rodríguez L; Edna-Estrada F; Castañeda-Orjuela C; De La Hoz-Restrepo F (Dove Medical Press, 2022)
Nelson J Alvis-Zakzuk,1,2 Diana Díaz-Jiménez,1 Pablo Chaparro-Narváez,1 Juan C Gutiérrez-Clavijo,1 Liliana Castillo-Rodríguez,1 Francisco Edna-Estrada,3 Carlos Castañeda-Orjuela,1 Fernando De La Hoz-Restrepo4 1Observatorio Nacional de Salud, Instituto Nacional de Salud, Bogotá, D.C., Colombia; 2Departamento de Ciencias de la Salud, Universidad de la Costa-CUC, Barranquilla, Colombia; 3Federación Colombiana de Obstetricia y Ginecología, Cartagena, Bolívar, Colombia; 4Grupo de Evaluación en Epidemiología y Salud Pública, Universidad Nacional de Colombia, Bogotá, D.C., ColombiaCorrespondence: Nelson J Alvis-ZakzukDepartamento de Ciencias de la Salud, Universidad de la Costa-CUC, Cl. 58 #55 - 66, Barranquilla, ColombiaEmail nalvis1@cuc.edu.coObjective: We aimed to estimate out-of-pocket (OOP) health expenditures and the indirect costs related to prenatal check-ups in pregnant women seen in a maternity hospital in the Colombian Caribbean region.Methods: We described the economic costs of pregnant women, with no age limits, who attended prenatal check-ups in a maternity hospital. To estimate OOP and indirect costs owing to prenatal check-ups in pregnant women, a survey was constructed, where the woman was asked about some sociodemographic variables, to characterize those attending the prenatal check-ups. Absolute and relative frequencies, averages and confidence intervals were used to characterize the population and estimate OOP and indirect costs in pregnant women. The latter were estimated from the percentile method. A bootstrapping was performed to reduce the bias within the analysis.Results: In total, 56 pregnant women were surveyed, with an average age of 25.9 years (± 6.2). All women surveyed had OOP associated to the prenatal check-up in at least one cost-item, and the OOP ranged between